2005
DOI: 10.1002/adma.200500752
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐Beam‐Assisted Lift‐Off Technique for Three‐Dimensional Micromachining of Freestanding Single‐Crystal Diamond

Abstract: Diamond is a very attractive material for micromachining: it has high mechanical hardness, high Young's modulus, a low coefficient of friction, high thermal conductivity, and a low thermal expansion coefficient. It is chemically inert and biocompatible. Optically, it is transparent over the widest range of the electromagnetic spectrum (from 220 nm to the far infrared), has a high refractive index, and exhibits a vast inventory of luminescent centers (> 500 electronic, > 150 vibrational), many of which are rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(118 citation statements)
references
References 18 publications
2
115
0
1
Order By: Relevance
“…Micromachining of diamond is presently being explored for similar purposes, see [24,25], and modelling has shown that suitable cavities are in principle fabricatable [26]. The application of diamond for quantum computing and quantum optics applications has recently been reviewed [27].…”
Section: Potential Implementationsmentioning
confidence: 99%
“…Micromachining of diamond is presently being explored for similar purposes, see [24,25], and modelling has shown that suitable cavities are in principle fabricatable [26]. The application of diamond for quantum computing and quantum optics applications has recently been reviewed [27].…”
Section: Potential Implementationsmentioning
confidence: 99%
“…22,23 All cross section lamellas were extracted from the center of the sample, i.e., the most homogeneous area, with thicknesses around 200 nm. Diffraction contrast observations were performed with a Jeol 1200EX and a Jeol 2010F microscopes operating at 120 keV and 200 keV, respectively.…”
mentioning
confidence: 99%
“…(ii) The 'lift-off' technique 65,70 , which consists of creating a sacrificial layer by irradiating the diamond with ions. This layer is removed after graphitizing it by annealing.…”
Section: Nanophotonics Componentsmentioning
confidence: 99%